Utilising LEGO® Six Bricks® to Enhance the Pedagogy of Pre-Service Teachers in South Africa - Breytenbach, Tarien; Marais, Elma; Botha, Carolina; Coertzen, Florence (Jurnal Paedagogy, 2025)
This study explores the potential of LEGO® Six Bricks®, a manipulative educational tool, to enhance the pedagogical skills of third-year pre-service teachers in South Africa. Employing participatory action learning and action research (PALAR), the study involved six third-year pre-service teachers from North-West University, Potchefstroom Campus. Data was generated using LEGO®-voice, reflective journalling and reflective group conversations during and after school-based teaching practice. Data analysis involved thematic content analysis and inductive analysis using ATLAS.ti 23 software These pre-service teachers not only had to reflect on their own perceptions regarding pedagogy and the role that pedagogy plays in being a teacher, but also on how a manipulative can be utilised as a teaching tool.  The findings in this study revealed that LEGO® Six Bricks® positively impacted pedagogical approaches despite challenges such as insufficient support from mentor teachers and resource constraints. This study contributes to the ongoing discourse on bridging the theory-practice gap in teacher education by integrating innovative, play-based learning tools.